A produção de artigos de opinião por alunos do ensinodo ensino fundamental: A construção da contra-argumentação mediada por operadores de conformidade e contraposição - Barros, João Batista da Silva (2016)
The present dissertation, characterized as an action research, evidences didactic-pedagogical actions developed with students of the 9th grade of Elementary School from a school of the municipal teaching network in João Pessoa. These actions aimed mainly more than making these students produce opinion articles, enabling them to study and reflect on the use of the operators of conformity and contraposition not exclusively by the classification bias, but by their possibilities of effective use in the text for the evidence and/or contraposition of arguments. Moreover, by assuming a didactic-pedagogical position that does not focus only on the study of language by a purely metalinguistic bias, but that also makes it effective throughout reflection on the possibilities of practical use of our linguistic instruments, we realize that this can only occur within a certain discursive / textual genre. Assuming this position, we need to be theoretically grounded to promote our work. In order to compose our theoretical basis on mother language teaching, even distinguishing the metalinguistic teaching from the epilinguistic one, we use the official documents that rule the Education in the country and theorists such as Antunes (2003, 2007), Callou (2014), Franchi (2006), Geraldi (2003), Neves (2007, 2012, 2014), Silva (2001), among others that study language and teaching as a way of promoting reflection on communication and on linguistics (inter)actions that we carry out on a daily basis. In order to enlighten us with regard to the studies on argumentation that is the essential mark of the discursive/textual genre essay we refer to Carel (2002), Ducrot (1987, 2009), Freitas (2008), Nascimento (2012), Nunes (2016), Pacheco (2016), Perelman (1987), and a few others who try to analyze this phenomenon of human communication and interaction. Finally, we need theoretical support regarding the concept of discursive / textual genre and how the use of operators is processed in an argumentative text. In this sense, they were essential the theoretical conceptions of Bakhtin (2011), Bräkling (2000), Bronckart (2006, 2012), Kersch (2014), Koch (2011), Koch and Elias (2016), Nascimento (2012), Rodrigues (2000) and others that are also dedicated to research the process of human communication and interaction through language. Once theoretically supported, we put into practice our planned didactic-pedagogical activities, thus effecting the intended teaching-learning process. After completing the applications, we defined a corpus of 12 texts (6 initial versions and 6 final versions) produced by the students in order to be analyzed. By making the comparative analysis between the initial and final productions of these students, we were able to perceive how much they evolved in relation to the expansion of their linguistic-discursive skills and abilities along the 20 classes taught, mainly regarding the capacity of using argumentative operators to evidence and/or oppose arguments within an essay.